Rising to the Challenge of Creating Equitable, Inclusive, and Compassionate School Communities in the Recovery Phase of the Pandemic: The Role of Aspiring Headteachers - Joan G. Mowat; Anna Beck (MDPI AG, 2023)
Concerns have been raised globally about the impact of the pandemic on the mental health and wellbeing of children and young people (CYP). How prospective headteachers rose to the challenge posed by the pandemic in supporting the wellbeing of their school communities and reaching out to the most vulnerable CYP and families during the recovery phase is the focus of this paper. It is a longitudinal, principally qualitative study conducted in two phases with 60 former students of the Into Headship programme in Scotland. Phase 2 of the study drew on the accounts of eight students drawn from the primary, secondary, and special education sectors using individual interviews and focus group discussions. This paper draws on the accounts of three secondary sector participants in interview. Data were analysed via thematic analysis using a modified framework of King and Horrocks. The respondents had encountered a wide range of challenges and had been highly proactive in their approach through adopting both targeted and universal approaches to meeting need and addressing inequalities. The findings of this paper should inform the development of headship preparation programmes globally and the responses of schools in the recovery phase, furthering our understanding as to what constitutes inclusion in education.